The study of mechanical properties of the polyaniline: Alcaúlan clays nanocomposite - M.Shabeeb, Ghufran; A.Sweaf, Abbas (Al-Qadisiyah Journal of Pure Science, 2017)
Intercalation composite of polyaniline and clay has been reported.The composite was prepared by in polymerization of aniline with "Alcaúlan" Clay.Were studied of the mechanical properties of polyaniline/ Alcaúlan clay. Which was prepared in Almokhtbroand accurate size equal to(≤ 250)μm. Mechanical properties are studing several variables such as the coefficient Jonk, tensile strength, elongation, fracture resistance and hardness.The results showed that the hardness of PAni/clay increase with increasing PAni/clay increase with temperature. Also fracture strength increase with increasing temperature